Construction and analysis tool design capture pengerih (stow net) used fishing village bay sub in waters kampar peninsula kampar peninsula pelalawan province riau - Amran '; Syofian '; Nofrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Stow net fishing gear used fisher bay is not effective to operate because the use of shortening with a value of 17.8 % on the body gear stow net cause the formation of a perfect in body construction with water thus affecting the shape of mesh openings and the mechanism of operation of the tool . Formations are good for shortening the fishing cape stow net used selukup is 15 % for mouth and body , and 10 % for the waist , tummy and pouch . Due to the characteristics of fast-flowing waters tend bumpy enough and strong , it is necessary to increase the buoyancy of 2.880 gf so well established tools when operated .Keywords : Capture Device Stow net , Construction and Analysis